ANALISIS KECEPATAN AMAN KAPAL UNTUK MENGHINDARI TUBRUKAN DI MT. BINTULU - Pranaja Nosana; Kurniawan Abadi; Rizal Rochmansyah; Nelfi Erlinda; Fahmi Uma Sangadji (STKIP Subang, 2026)
Safe speed is a condition that must and is mandatory to be applied on board aship so that the vessel can operate safely and does not endanger the ship itself, the cargo, or the marine environment through which it sails. However, there are still instances where safe speed is neglected due to human error. The method used in this study is a qualitative method, with the research location on board MT. BINTULU. The data used consist of primary data and secondary data. Data collection in this study was carried out through observation, interviews, and documentation techniques. The results of this study indicate that the impacts and risks of not optimally applying safe speed when navigating through shipping lanes include collisions, grounding, and other navigational hazards. However, the hazards most frequently experienced due to the less optimal application of safe speed in shipping lanes are collisions and ship grounding. The optimal application of safe speed can be achieved based on the competence and knowledge of human resources who have mastery of the application of P2TL, particularly Rule 6, thereby accidents that occur can be minimized or even eliminated.